Iris Ring Melanoma Presenting as Scleral Pigmentation - Matej Zupan; Alenka Lavrič; Jože Pižem; Katrina Novak Andrejčič (Case Reports in Ophthalmological Medicine, 2022)
To report a patient with a very rare variant of iris melanoma that grows in the shape of a ring (ring melanoma). A 65-year-old patient was examined because of a pigmented lesion on the sclera. After a complete ophthalmic and ultrasound examination, a ring melanoma was diagnosed. Enucleation of the affected eye was performed, and histology report confirmed iris ring melanoma. This type of malignancy represents an exceedingly rare variant of uveal melanoma, and because of atypical clinical picture, it can be easily overlooked or misdiagnosed, which often delays adequate treatment. Gonioscopy, transillumination, and ultrasound help us to recognize and diagnose ring melanoma. Suspicion should be raised with a clinical picture that shows unilateral pigmentary glaucoma. The objective of this presentation is to describe and outline the challenging diagnosis and management of this rare disease entity.